Comparison of ISS, NISS, and RTS score as predictor of mortality in pediatric fall. Issue 1 (8th August 2017) - Soni, Kapil Dev; Mahindrakar, Santosh; Gupta, Amit; Kumar, Subodh; Sagar, Sushma; Jhakal, Ashish
Abstract: Background: Studies to identify an ideal trauma score tool representing prediction of outcomes of the pediatric fall patient remains elusive. Our study was undertaken to identify better predictor of mortality in the pediatric fall patients. Methods: Data was retrieved from prospectively maintained trauma registry project at level 1 trauma center developed as part of Multicentric Project—Towards Improving Trauma Care Outcomes (TITCO) in India. Single center data retrieved from a prospectively maintained trauma registry at a level 1 trauma center, New Delhi, for a period ranging from 1 October 2013 to 17 February 2015 was evaluated. Standard anatomic scores Injury Severity Score (ISS) and New Injury Severity Score (NISS) were compared with physiologic score Revised Trauma Score (RTS) using receiver operating curve (ROC). Results: Heart rate and RTS had a statistical difference among the survivors to nonsurvivors. ISS, NISS, and RTS were having 50, 50, and 86% of area under the curve on ROCs, and RTS was statistically significant among them. Conclusions: Physiologically based trauma score systems (RTS) are much better predictors of inhospital mortality in comparison to anatomical based scoring systems (ISS and NISS) for unintentional pediatric falls.